The Evolution of Marketing in the Digital Age: Trends, Challenges, and Opportunities - López Martínez , Sergio Andrés; Lancheros Acevedo, Helbert Yadir (Universidad Francisco de Paula Santander, 2025)
This text analyzes the evolution of marketing in the digital age, highlighting its trends, challenges, and opportunities. It establishes the context and relevance of the topic, while identifying the challenges faced by companies, especially small and medium-sized ones, in adopting digital marketing strategies. Subsequently, key concepts such as digitalization, digital marketing, and artificial intelligence are reviewed. This study was developed through a qualitative and exploratory approach. The results and analysis emphasize the importance of training and selecting suitable tools for business success. The discussion and conclusion highlight the need for adaptation and innovation in digital marketing, as well as addressing challenges related to tool adoption and training, and exploring artificial intelligence-related topics.